Whose Choice Is It? Shared Decision Making in Nephrology Care. Issue 2 (22nd February 2013) - Murray, Mary Ann; Bissonnette, Janice; Kryworuchko, Jennifer; Gifford, Wendy; Calverley, Sharon
Abstract Patients living with end‐stage renal disease (ESRD) are faced with numerous decisions across the trajectory of their illness. Shared decision making (SDM) offers a patient‐centered approach to engage patients in decision making in meaningful ways. Using an SDM approach, patients and providers collaborate to make healthcare decisions by taking into account the best available empirical evidence, in conjunction with the patient's values, preferences, and individual circumstances. In this article, we outline the principles of SDM; highlight the broad range and context of decisions faced by patients living with ESRD; review decision‐support interventions; and consider opportunities and challenges for implementing SDM into usual ESRD practice. A summary of current knowledge and areas for research and further investigation concludes the paper. Because nephrology team members spend a lot of time interacting with patients during treatments and follow‐up care, they are well positioned to engage in SDM. Healthcare systems need innovation in communication to ensure the ethical application of important technological improvements in renal treatments, and to ensure that patient decision‐support processes are available. SDM is a promising innovation to support the recalibration of care for patients living with end‐stage renal disease.